Studi Deskriptif Karakteristik Dukungan Suami Dalam Pemberian ASI Eksklusif - gunarmi; Siti Maimunah; Eka Vicky Yulivantina (Universitas Yatsi Madani, 2023)
Exclusive breastfeeding is an effort to prepare a healthy next generation from an early age. In providing breast milk, mothers need support from various parties, one of which is their husband. Social support is defined as a source of support obtained from other people, which can be from various sources, one of which is a partner or loved one. Husbands are one of the important people in a mother's life. The aim of this research is to determine the characteristics of husbands in providing exclusive breastfeeding to breastfeeding mothers in Kepuharjo, Cangkringan. This research is a quantitative descriptive study with a cross sectional approach. The research results show that the majority of the frequency distribution of husbands' informative support is in the good category, namely 52.3%. The majority of the frequency distribution of husbands' emotional support is in the good category, namely 55.8%. The frequency distribution of the majority of husbands' instrumental support is in a balanced category between good and poor, namely 50%. The majority of husbands' appraisal support frequency distribution is in the good category, namely 54.7%.